In vitro cytotoxic effects and ultrastructural changes in myocardial (H9c2) and neuroblastoma (neuro-2a) cell lines following exposure to three different cardiac glycosides - Botha, C.J. (Christoffel Jacobus) (University of Pretoria, 2019)
Dissertation (MSc)--University of Pretoria, 2018.